The formula of tan(x+y+z) is given as follows:

tan(x+y+z) = $\dfrac{\tan x +\tan y+\tan z – \tan x \tan y \tan z}{1-\tan x \tan y-\tan y \tan z-\tan z \tan x}$.

In this post, let us learn how to prove the formula of tan(x+y+z).

## Proof of tan(x+y+z) Formula

We will use the formula

tan(a+b) = $\dfrac{\tan a +\tan b}{1-\tan a \tan b}$.

Put a=x+y and b=z.

Now, tan(x+y+z) = tan((x+y)+z)

⇒ tan(x+y+z) = $\dfrac{\tan (x+y) +\tan z}{1-\tan (x+y) \tan z}$

= $\dfrac{\frac{\tan x +\tan y}{1-\tan x \tan y} +\tan z}{1- \frac{\tan x +\tan y}{1-\tan x \tan y} \tan z}$

= $\dfrac{(\tan x +\tan y)+(1-\tan x \tan y)\tan z}{(1-\tan x \tan y)-(\tan x +\tan y)\tan z}$

= $\dfrac{\tan x +\tan y+\tan z – \tan x \tan y \tan z}{1-\tan x \tan y-\tan y \tan z-\tan z \tan x}$.

So the formula of tan(x+y+z) is equal to (tanx + tany +tanz – tanx tany tanz)/(1- tan x tany – tany tanz – tan z tanx).

**More Formulas:**

## FAQs

### Q1: What is the formula of tan(x+y+z)?

**Answer:** The formula of tan(x+y+z) is (tanx + tany +tanz – tanx tany tanz)/(1-tan x tany – tany tanz -tan z tanx).

### Q2: What is the formula of tan(a+b+c)?

**Answer:** The formula of tan(a+b+c) is equal to (tana + tanb +tanc – tana tanb tanc)/(1- tana tanb – tanb tanc -tanc tana).